The Criminal Procedure Code of the Republic of Belarus: 20 years of improvement - Samaryn, Vadzim I.; Danilevich, Anatol A.; Petrova, Olga V. (Journal of the Belarusian State University. Law, 2019)
The article reveals the development of criminal procedure legislation over the 20 years of force of the Criminal Procedure Code of the Republic of Belarus. Analysis of the content of this legal act allows us to note the conformity, consistency of the content of its provisions with the Constitution of the Republic of Belarus, reflection in the latter of the socio-economic, political and other relations existing in the state and trends of positive development of them, as well as achievements of the practice of criminal prosecution and criminal justice bodies. It is noted that the international legal paradigm of the modern criminal procedure also influenced the content of the Code. The article identifies some problematic aspects of the current version of the Code (turning the stage of initiation of a criminal case into a «quasi preliminary investigation», the need to expand the ability of the court of the second instance to evaluate evidence, etc.), and also set possible directions for its further improvement (introduction of mediation, sentence of appeal, intermediating the development of modern technology, etc.). It is shown the need to harmonise criminal procedure law within the EAEU.
Keywords: criminal procedure; criminal procedural law; Code of Criminal Procedure; legislation improvement